Pengaruh Lingkungan Kerja dan Motivasi Terhadap Kinerja Pegawai pada Bagian Sosial Sekretariat Daerah Kabupaten Bekasi - Ratna Emaliah (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2017)
This study aims to determine the effect of the working environment and Motivation on Employee Performance in Social Section Sekretaris Daerah Bekasi. The study population is with research samples totaling 29 respondents indicated the following results: First: there is a positive and significant impact on the performance of the Work Environment Officer at the Social Section Sekretaris Daerah Bekasi, with a correlation coefficient Y = 49 520 + 0580 X1, while the coefficient of determination between the variables on the performance of Employee Work Environment obtained by the 0.30 or in percentage 30 00 percent, t-test were obtained for 5428. > 2,045 Second: there is a positive and significant effect of work motivation on employee performance with a correlation coefficient Y = 65 433 + 0.187X2, while the coefficient of determination between variable work motivation on employee performance is obtained, ie, 0.35 or in percentage 35.00 percent, t-test were obtained for 7692> t-table 2045. Third: there is a positive and significant impact together variable Work Environment and Motivation on Employee Performance with a correlation coefficient Y = 56 436 + 0.018 X1 + 0185 X2, while the coefficient of determination correlation ® positive (0.361) that t was obtained for 7692> t-table 2045